COMPARATIVE STUDY OF TIME ECHO VARIATIONS IN THE METABOLITE VALUES MR BRAIN SPECTROSCOPY - Dewi Susanto, Revina; Yuliana F., Ayu; Serfina F., Eunike; Catharina R., Celine; Amnesti, Merry; Masrochah , Siti; Choridah, Lina (Journal of Vocational Health Studies, 2024)
Background: MR spectroscopy is an additional sequence to evaluate lesion characteristics in the brain. Time Echo (TE) is crucial for analyzing MR spectroscopy metabolite. Purpose: This study aims to evaluate the best TE variations during MR spectroscopy examinations in brain lesions. Method: This research is an experimental quantitative study. Researchers used five samples focusing on the results of head multi-voxel spectroscopy charts with clinical lesions or masses that had been taken twice using TE 35 and TE 144. At each TE in each sample, three voxel areas were measured, namely normal, perilesional, and lesion. Each spectroscopy data result is processed individually through READY View software, automatically producing a spectroscopy graph pattern. The required data in this study is the value of each head spectroscopy metabolism: N-Acetyl Aspartate (NAA), Choline (Cho), Creatine (Cr), Myo-Inositol (MI), Lipids Lactate (LL). All statistical tests used the SPSS v.26 application. Result: Based on Paired T test results, NAA, Cho, Cr, and MI metabolites have p-values that account for 0.779 > 0.05; 0.179 > 0.05; 0.581 > 0.05; and 0.057 > 0.05. Based on the Wilcoxon Sign Rank test, the LL metabolite showed a p-value of 0.460 > 0.05. Conclusion: There is no significant difference between TE 35 ms and TE 144 ms during MR spectroscopy examinations.